2021
DOI: 10.1002/ctm2.341
|View full text |Cite
|
Sign up to set email alerts
|

LRRK2 inhibition potentiates PARP inhibitor cytotoxicity through inhibiting homologous recombination‐mediated DNA double strand break repair

Abstract: LRRK2 inhibitor GSK2578215A suppresses HR and sensitizes ovarian cancer cells to PARP inhibitor. LRRK2 inhibition impedes the recruitment of RAD51 by disrupting the interaction of RAD51 and BRCA2. High expression of LRRK2 is associated with poor survival of ovarian cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…A specific LRRK2 rs10878441 CC genotype has been linked to a poorer prognosis in Chinese breast cancer patients [ 43 ]. High LRRK2 expression has also been associated with poorer survival in ovarian cancer [ 44 ]. It was also demonstrated that inhibiting LRRK2 promoted toxicity of PARP inhibitor by reducing homologous recombination-mediated DNA double strand break repair [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A specific LRRK2 rs10878441 CC genotype has been linked to a poorer prognosis in Chinese breast cancer patients [ 43 ]. High LRRK2 expression has also been associated with poorer survival in ovarian cancer [ 44 ]. It was also demonstrated that inhibiting LRRK2 promoted toxicity of PARP inhibitor by reducing homologous recombination-mediated DNA double strand break repair [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…High LRRK2 expression has also been associated with poorer survival in ovarian cancer [ 44 ]. It was also demonstrated that inhibiting LRRK2 promoted toxicity of PARP inhibitor by reducing homologous recombination-mediated DNA double strand break repair [ 44 ]. LRRK2 is also involved in the ATM-Mdm2-p53 pathway that regulates cell proliferation in response to DNA damage [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue microarrays contained 128 ovarian cancers with clinical characteristics were purchased from Alenabio and Shanghai Outdo Biotech Company. Immunohistochemical (IHC) staining was carried out as previously described ( Chen et al, 2021 ). All samples were scored by three independent pathologists.…”
Section: Methodsmentioning
confidence: 99%
“…LRRK2 inhibitors decreased the production of tumor necrosis factor‐α by dextran sulfate sodium‐induced colitis in a mouse model and in dendritic cells from patients with Crohn's disease 6,7 . LRRK2 inhibition or depletion sensitized ovarian cancer cells with high expression of LRRK2 to poly (ADP‐ribose) polymerase (PARP) inhibitors, including olaparib, indicating that a combination therapy with LRRK2 and PARP inhibitors could be a promising therapeutic strategy to overcome resistance to PARP inhibitors in ovarian cancer 8 . Therefore, LRRK2 inhibitors have received considerable attention as therapeutic targets.…”
Section: Figurementioning
confidence: 99%